The wonder of their voices the 1946 Holocaust interviews of David Boder - Rosen, Alan (Alan Charles) (Oxford University Press, 2011)
Arguing that early postwar Holocaust testimony was plentiful and significant in its own right, Rosen highlights the Russian-born American psychologist David Boder, who in 1946 was among the earliest to interview Holocaust survivors in DP camps and, as far as we know, the first to audio record their testimony.